Anoctamin 1/TMEM16A controls intestinal Cl- secretion induced by carbachol and cholera toxin - Lee, Byeongjun; Hong, Gyu-Sang; Lee, Sung Hoon; Kim, Hyungsup; Kim, Ajung; Hwang, Eun Mi; Kim, Jiyoon; Lee, Min Goo; Yang, Jin-Young; Kweon, Mi-Na; Tse, Chung-Ming; Mark, Donowitz; et al. (생화학분자생물학회, 2019)
Calcium-activated chloride channels (CaCCs) mediate numerous physiological functions and are best known for the transport of electrolytes and water in epithelia. In the intestine, CaCC currents are considered necessary for the secretion of fluid to protect the intestinal epithelium. Although genetic ablation of ANO1/TMEM16A, a gene encoding a CaCC, reduces the carbachol-induced secretion of intestinal fluid, its mechanism of action is still unknown. Here, we confirm that ANO1 is essential for the secretion of intestinal fluid. Carbachol-induced transepithelial currents were reduced in the proximal colon of Ano1-deficient mice. Surprisingly, cholera toxin-induced and cAMP-induced fluid secretion, believed to be mediated by CFTR, were also significantly reduced in the intestine of Ano1-deficient mice. ANO1 is largely expressed in the apical membranes of intestines, as predicted for CaCCs. The Ano1-deficient colons became edematous under basal conditions and had a greater susceptibility to dextran sodium sulfate-induced colitis. However, Ano1 depletion failed to affect tumor development in a model of colorectal cancer. We thus conclude that ANO1 is necessary for cAMP-and carbachol-induced Cl- secretion in the intestine, which is essential for the protection of the intestinal epithelium from colitis.